Industrialização e emprego formal: uma análise para os municípios da região metropolitana do Cariri nos anos de 1990 e 2000 - Nascimento, Ana Lourdes Fernandes (2013)
The Northeast has a record of fighting to reduce disparities. In late 1950, the state intervened through SUDENE, organizing and planning the promotion of development through industrialization. This study aims to identify the characteristics of the industrialization of the Northeast and evolution of formal employment in the metropolitan area of Cariri, located in the southern state of Ceará, in the case of the municipalities of Crato, Juazeiro do Norte and Barbalha (CRAJUBAR) in decades of 1990 and 2000. The assumption permeates the SUDENE with public policies to encourage the industry, causing profound changes in the cities studied. The results indicate that the Cariri since the 1960 has been benefiting the programs implemented by SUDENE. With the implementation of these programs, with in a set of circumstances based on local vocations and state policies, there was a spatial distribution industry, triggering a growth and development on the provision of formal jobs in the industrial sector